POPULATION DYNAMICS - Utami, Pertiwi; Febriyanti, Delia; ulfah, Mardia (LPPM Universitas Bina Bangsa, 2024)
Demography is writings about people or human population. Demography is also known as population science, which is the science that studies the dynamics of human population. Demography comes from a combination of Greek words, namely demos meaning people or population, while graphein means writing or records. Demography studies the population, the most important of which is studying fertility or birth, mortality or death and mobility. Population affects the economic growth of a region. Population plays an important role in the economy with rapid growth throughout the world. Population growth will have a major impact on the country's economy, as is the case in developing countries including Indonesia. The implications of population size, development, and quality are very important to consider in planning for proper economic development in the future. Population dynamics are conditions in which the population structure, number, and distribution change due to demographic processes such as birth, death, and migration. Population growth, according to Lucas, Donald & Young (1990), is influenced by three main elements, namely fertility (birth), mortality (death), and migration. The fertility rate has a positive effect on population growth or increases the population, while the mortality rate has a negative effect or reduces the growth rate.